Serum levels of interleukin-6 are linked to the severity of the disease caused by Andes Virus - Angulo, Jenniffer; Martínez-Valdebenito, Constanza; Marco, Claudia; Galeno, Héctor; Villagra, Eliecer; Vera, Lilian; Lagos, Natalia; Becerra, Natalia; Mora, Judith; Bermúdez, Andrea; Díaz, Janepsy; Ferrés, Marcela; et al. (PLOS Neglected Tropical Diseases, 2017)
Author summary Andes virus (ANDV) causes hantavirus cardiopulmonary syndrome (HCPS) that is characterized by the development of vascular leakage syndrome, eventually leading to massive pulmonary edema, shock and, in many cases, death. To date, no FDA-approved immunotherapeutics, specific antivirals, or vaccines are available for use against HCPS. Patient survival rates hinge largely on early virus diagnosis, hospital admission and aggressive pulmonary and hemodynamic support in an intensive care unit. Individual host factors associated with the outcome of an ANDV infection are poorly known, and such knowledge could allow the disease progression of hospitalized patients to be predicted, resulting in individualized treatment. In this study, we show that serum levels of IL-6 at the time of hospitalization in ANDV-infected patients are associated with the severity of the clinical outcome of ANDV-induced disease. Therefore, these finding suggest that determining IL-6 levels at the time of admission to the hospital could be useful to predict the progression of ANDV-induced disease.